PERAN PENDAMPING LOKAL DESA DALAM PEMBANGUNAN DESA BABAI KECAMATAN KARAU KUALA KABUPATEN BARITO SELATAN - Latifah; Taufik Arbain; Muslih Amberi (Jurnal PubBis, 2022)
ABSTRACT Village development that is still not optimal is a problem that is closely related to the role of lokal assistants that are not optimal. This can be seen from the village development process how the role of the lokal village assistant as a facilitator and communicator and what obstacles are faced by the role of the village lokal companion which causes his role as a companion is still not optimal. The results showed that the role of lokal assistants in Babai Village was still not optimal, judging from their role as facilitators and communicators. As a facilitator in the planning, community empowerment and evaluation stages, it has been going well but in the implementation stage, this is still lacking, as can be seen from the lack of community participation during the implementation of development. As a communicator in the stage of community empowerment and development evaluation is quite good but in the planning and implementation stage of development is still not good, this can be seen when lokal village assistants are unable to provide solutions in planning and implementing development in the village. Influencing factors are coordination, workload and quality of human resources as lokal companions to the village. The results of this study are suggested to form an assessment team to conduct evaluations, openness in the process of recruiting lokal village assistants, the need for accurate village mapping and adjusting to the residence of lokal village assistants, providing supporting work facilities and infrastructure and socialization. Keywords :The role; lokal village assistants; Village Development